Pressing iron ore concentrate in a pilot-scale HPGR. Part 2: Modeling and simulation. (15th August 2019) - Campos, Tulio M.; Bueno, Gilvandro; Barrios, Gabriel K.P.; Tavares, Luís Marcelo
Graphical abstract: Highlights: Poor predictions when applying directly Torres and Casali model to data. Modifications to the model have been proposed. Modifications in capacity and power equations have been successfully implemented. Use of non-normalizable breakage function led to improved product size distribution. Comparisons showed benefit of edge recycle in comparison to single and double-stage. Abstract: The roller press, also called high-pressure grinding rolls (HPGRs), has been successfully used for over 25 years in increasing the surface area of iron ore concentrates for pellet feed production prior to green pellet formation. In spite of the long track record of application, there have been no systematic mathematical modeling studies of that operation in pellet feed production. The paper initially analyzes the direct application of Torres and Casali model to data from roller pressing of iron ore concentrate fines at a pilot-scale facility. Inadequacies have been identified and modifications for improved prediction of power, throughput and product size distribution for the case in question have been proposed. Parameters from two of the submodels (power and breakage) were amenable to fitting on the basis of data from a single experiment. Simulation results with the modified version of the model agreed well with experiments. Finally, different strategies of operation of the roller press in pellet feed pressing, namely single pass, double-stage pressing and single-stage with recycle of the edge product were then analyzed on the basis of experiments and simulations, demonstrating the benefit of edge recycling.